Mapping of Medical and Health Studies in Bosnia and Herzegovina using Scopus - Ahmed, KK Mueen; Kumar P, Dharani; Sab M, Chaman (Journal of Data Science, Informetrics, and Citation Studies)
This study analyses the research activities of Bosnia and Herzegovina in Medical and Health studies during 2012 – 2021, based on the total publication output, its growth rate, quality of papers published, and rank of Bosnia and Herzegovina in the global context. Patterns of international collaborative research output and major partner countries of Bosnia and Herzegovina are also discussed. This study also evaluates the research performance of different institutions and characteristics of published literature in Bosnia and Herzegovina and foreign journals. The Medical and Health published literature data has been retrieved by using the Scopus database. Bosnia and Herzegovina hold 93rd rank among the productive countries in medical and health research.
Keywords: Medical and Health Studies; Mapping; Bosnia and Herzegovina; Scopus; Scientometric Study.